Barley and Malt as Base Ingredients for the Production of New Bio- Functional Foods - Cian, Raúl Esteban (2023)
This work aimed to evaluate the chemical composition, bioactive compounds (phenolics andγ-aminobutyric acid, GABA), and antioxidant properties of different barley varieties(Overture, Charles, Sinfonía, Montoya, and Andreia) and their malts to weigh up them aspotential ingredients for producing new bio-functional foods. For this, five barleys and fivemalts obtained from them were studied. Regarding chemical composition, total starch wasthe main component (≈62%) of barleys followed by total dietary fiber (≈22.6%) and proteins(≈9.5%). Potassium and phosphorus were the most abundant elements, with mean valuesbeing 3746.1 and 3679.1 g 100g-1d.w., respectively. Regarding the free amino acid profile,the proportion of hydrophobic free amino acids was higher than that of branched-chainamino acids or sulfur-containing amino acids and the mean value of GABA was 8.8 mg 100g-1.Ferulic acid was the most abundant free phenolic acid detected in the different barleys,followed by coumaric acid. All barley extracts showed ABTS and DPPH inhibitory activities and ferric-reducing antioxidant power (FRAP). As expected, total starch, total dietary fiber, and crude fat contents of malts were lower than those found for barley. However, the malting process increased GABA, ferulic acid, hydrophobic free amino acids, branched-chain amino acids, and sulfur amino acid contents. Additionally, the antioxidant properties of malts were higher than those obtained for barleys. Barley flour could be successfully used as a bio-functional ingredient in many foods. Furthermore, given the high content of soluble solids (mainly carbohydrates, antioxidant compounds such as free phenolic acids and free amino acids, and GABA), malted flours would be novel ingredients for preparing beverages with bio-functional properties.